2014
DOI: 10.1002/14651858.cd004695.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous or extended cycle vs. cyclic use of combined hormonal contraceptives for contraception

Abstract: The 2014 update yielded four additional trials but unchanged conclusions. Evidence from existing randomized control trials comparing continuous or extended-cycle CHCs (greater than 28 days of active combined hormones) to traditional cyclic dosing (21 days of active hormone and 7 days of placebo, or 24 days of active hormone and 4 days of placebo) is of good quality. However, the variations in type of hormones and time length for extended-cycle dosing make a formal meta-analysis impossible. Future studies shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 63 publications
1
96
0
9
Order By: Relevance
“…Moreover, the few studies that have assessed women's experiences have been limited in scope and have most often used adherence to COCPs as a 'proxy' measure of satisfaction (Edelman et al, 2010). The findings of this exploratory study provide more detailed information about women's actual experiences of tailored COCP use.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the few studies that have assessed women's experiences have been limited in scope and have most often used adherence to COCPs as a 'proxy' measure of satisfaction (Edelman et al, 2010). The findings of this exploratory study provide more detailed information about women's actual experiences of tailored COCP use.…”
Section: Discussionmentioning
confidence: 96%
“…There have also been many more studies of women's attitudes toward hypothetical use of extended-use pill regimes (Den Tonkelaar and Oddens, 1999;Glasier et al, 2003Glasier et al, , 2008Andrist et al, 2004) than of their actual use of continuous COCPs. In a Cochrane review of use of extendedcycle versus standard use of COCPs, the authors concluded that further research on women's satisfaction and menstrual-associated symptoms was needed (Edelman et al, 2010). Qualitative research is important to better understand contraceptive use behaviors and the barriers or problems related to extended-use contraceptive methods (Sundstrom, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that menstrual symptoms of headaches, genital irritation, tiredness, bloating, and menstrual pain may be less in extended-cycle regimens. 24 …”
Section: Combined Oral Contraceptivesmentioning
confidence: 99%
“…17 Oral contraceptive pills reduce menstrual blood flow 35% to 69%. 17 Bleeding patterns appear to be improved with continuous as opposed to cyclic administration, 18 and with pills containing more than 20 mg of ethinyl estradiol vs pills with 20 mg or less. 19 In a randomized trial of continuous administration, combined oral contraceptives containing 1 mg of norethindrone resulted in fewer days of bleeding and spotting than preparations containing 0.1 mg of levonorgestrel.…”
Section: Hormonal Management Of Hmb In Women With Bleeding Disordersmentioning
confidence: 99%